2019
DOI: 10.1111/jipb.12729
|View full text |Cite
|
Sign up to set email alerts
|

Short Panicle 3 controls panicle architecture by upregulating APO2/RFL and increasing cytokinin content in rice

Abstract: Inflorescence architecture is a major determinant of spikelet numbers per panicle, a key component of grain yield in rice. In this study, Short Panicle 3 (SP3) was identified from a short panicle 3 (sp3) mutant in which T‐DNA was inserted in the promoter of SP3, resulting in a knockdown mutation. SP3 encodes a DNA binding with one finger (Dof) transcriptional activator. Quantitative real time (qRT)‐PCR and RNA in situ hybridization assays confirmed that SP3 is preferentially expressed in the young rice inflore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 59 publications
0
15
0
1
Order By: Relevance
“…These transcriptional regulators participate in plant growth, development and other processes, including biotic and abiotic stress responses (Yanagisawa, ; Gabriele et al ., ; Noguero et al ., ; Renau‐Morata et al ., ; Rymen et al ., ; Zang et al ., ). Under most conditions, the roles of DOF proteins in these physiological processes involve plant hormones (Gabriele et al ., ; Boccaccini et al ., ; Rymen et al ., ; Huang et al ., ). Ethylene is a crucial, simple gaseous phytohormone (Achard et al ., ; Van de Poel et al ., ) whose biosynthesis is highly regulated at the transcriptional and post‐transcriptional levels (Argueso et al ., ; Yoon, ; Lee & Yoon, ).…”
Section: Discussionmentioning
confidence: 97%
“…These transcriptional regulators participate in plant growth, development and other processes, including biotic and abiotic stress responses (Yanagisawa, ; Gabriele et al ., ; Noguero et al ., ; Renau‐Morata et al ., ; Rymen et al ., ; Zang et al ., ). Under most conditions, the roles of DOF proteins in these physiological processes involve plant hormones (Gabriele et al ., ; Boccaccini et al ., ; Rymen et al ., ; Huang et al ., ). Ethylene is a crucial, simple gaseous phytohormone (Achard et al ., ; Van de Poel et al ., ) whose biosynthesis is highly regulated at the transcriptional and post‐transcriptional levels (Argueso et al ., ; Yoon, ; Lee & Yoon, ).…”
Section: Discussionmentioning
confidence: 97%
“…SP3 is expressed at the branch primordia of the young panicles. The mutant sp3 had an altered CK homeostasis wherein CK catabolism genes (four members of OsCKX gene family) were remarkably upregulated and CK biosynthesis genes (OsIPT3 and OsIPT7) were drastically downregulated, thus resulting in an overall reduction in the CK levels (Huang et al, 2019) (Figure 1).…”
Section: Cytokininsmentioning
confidence: 99%
“…plantbiology.msu.edu) and NCBI (https://www.ncbi.nlm.nih. gov/) (Huang et al, 2018). A total of 30 Dof genes were identified.…”
Section: Haplotype Construction and Haplotype-based Association Analysismentioning
confidence: 99%
“…In our study, there were 19 genes ( Table 2) whose knockout mutants had heading date that were indistinguishable from wild type. Phylogenetic analysis showed that six pairs of genes, OsDof1 and OsDof29, OsDof2 and OsDof23, OsDof9 and OsDof18, OsDof12 and OsDof26, OsDof13 and OsDof30, and OsDof24 and OsDof25, share a very conserved gene structure outside the Dof domain (Huang et al, 2018), which is probably responsible for their similar functions. For example, knockout mutants of both OsDof1 and OsDof29 promoted flowering time under LD (Table 3).…”
Section: There Is Functional Redundancy and Differentiation Among Dofmentioning
confidence: 99%
See 1 more Smart Citation